Sosialisasi Kegiatan Penyuluhan UMKMMewujudkan Perekonomian Masyarakat Yang Mempunyai Potensi Dan Peran Strategis Menurut Undang-Undang No. 20 Tahun 2008 - Abdul Atsar; Aryo Fadlian (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
The government has enacted Law Number 20 Year 2008 concerning Micro, Small and Medium Enterprises, but in reality there are still many people who do not yet have the interest to form MSMEs. This is due to residents not understanding the rules that apply. The method of community service is in the form of lectures. Lecturers as lecturers, and village officials as participants. Before the lecture, participants were asked to answer the pre-test questionnaire. After the material and questions and answers, participants were asked to fill in the post-test questionnaire. Based on the results of the activity it appears that increasing public understanding of MSMEs. This can be proven by various questions raised by participants and the results of the participant questionnaire assessment. Participants have understood the position of the community that has potential and strategic roles in realizing economic development, especially in Dewi Sari Village, Kec. Rengasdengklok District. Karawang, establish and manage MSMEs and so on. It is recommended that activities like this can be done routinely so that the existing MSMEs continue to grow so as to increase the income per capita of the community.